AN ANALYSIS OF SARCASM ON HATE SPEECH UTTERANCES ON JUST JARED INSTAGRAM ACCOUNT - Tirta Atma Pasa; Nuriadi; Husnul Lail (Program Studi Pendidikan Bahasa Inggris, 2021)
This research focuses on how sarcasm on hate speech is used by the followers of Just Jared’s account on Instagram. The purposes are to investigate what maxims are violated in the sarcastic comments made by the IG followers, which violation of maxim is the most dominant, and what factors cause hate speech in the comment. There were 50 comments collected as the primary source of data. The comments were those from the October 2019 to May 2020’s posts. Grice’s theory of maxims that classifies the rules of conversation into the maxims of quality, quantity, manner, and relevance was used to decide whether the comments violated the maxims or not. The results show that the analyzed data were proven to contain violation of the Gricean maxims that included violations of: the maxim of manner (17 comments), the maxim of quality (11 comments), the maxim of relevance (8 comments), and the maxim of quantity (4 comments). Besides single violation, some comments contain mixed violations that included the combinations of: the maxim of quantity and relevance (3 comments), the maxims of manner and relevance (3 comments), the maxim of quality and relevance (2 comments), and the maxim of quality and manner (2 comments). While violation of the maxim of manner records the highest (34%) in the data, combinations of violation of the maxim of quality-relevance and the maxim of quality-manner record the lowest (4.0%). Factors that motivate people to these violations are mostly due to the absence of providing brief, clear, and orderly information in the comments, the cultural value in the western countries that gives people the right and privilege to speak freely, the exaggeration for seeking other people’s attention, and the ego that enhances self-importance among individuals while at the same time diminishing others’.